Dyeing of Polypropylene Blends by Using Microwave Energy - (:unkn) unknown (My University, 2017)
In this work, C.I. Disperse Blue 79 was used to dye 100 % isotactic polypropylene (iPP) fibers, the most widely used fiber in the industry, 100 % linear low density polyethylene (LLDPE) polymer fibers and ternary polymer blends obtained from four different proportions of these polymer fibers with an elastomer of ethylene-vinyl acetate (EVA) in the absence and presence of microwave. The samples were tested for color measurement, color fastness, mechanical and morphological properties. The results of the investigation show that addition of up to 15% EVA in ternary polymer blends results in good color and mechanical properties for both dyeing methods in both the absence and presence of microwave energy. The SEM images indicate there is no porosity on the surfaces of the iPP/LLDPE/EVA ternary polymer blends dyed in the presence of microwave energy. Using microwave energy for dyeing provided a saving of almost 90% of the time normally required and thus a significant amount of energy.